Linalool induces relaxation of the mantle of golden apple snail (Pomacea canaliculata) - ADRIANE E. BIANCHINI; SHARINE N. DESCOVI; BERTA M. HEINZMANN; BERNARDO BALDISSEROTTO (Anais da Academia Brasileira de Ciências, 2021)
Abstract The objective of this study was to evaluate the possible relaxing effect of essential oils (EOs) (Aloysia triphylla and Lippia alba) and phytochemicals (citral and linalool) in the gastropod Pomacea canaliculata. Animals were exposed to compounds at the concentrations range of 25-750 µL L–1. Magnesium chloride (MgCl2, 10-50 g L–1) and control group (ethanol 6.75 mL L–1, highest concentration used for treatment dilution) were also tested. The EOs, citral and MgCl2 had no relaxing effect at the concentrations range tested, and citral caused aversive behavior (closure of the operculum) from 90 μL L–1. Exposure to linalool at 25, 50, 100, 200 and 400 µL L-1 relaxed 28, 76, 88, 96 and 100% of the animals, respectively. The concentrations of 25, 50 and 400 µL L-1 differed statistically from each other, while 100 and 200 µL L-1 were equal to 50 and 400 µL L-1. All animals recovered up to 40 min, except at of 400 µL L-1. Linalool is effective for relaxing P. canaliculata and can be useful in management techniques that require relaxation. However, further studies are needed to certify whether linalool is appropriate for maintaining animal welfare in invasive procedures that require total insensitivity.